Influence of HRM Factors on CWS Success in Foreign Countries - Zainul Hidayat; Ermawati, Emmy; Yatminiwati, Mimin (Jurnal Ilmu Manajemen Advantage, 2024)
This study aims to analyze the development, benefits, and implications of coworking spaces (CWS) as a flexible and collaborative modern work solution, as well as the factors influencing their success in various countries. Changes in the global economic system, driven by advancements in information and communication technology, have transformed work methods and increased the number of self-employed and freelancers. In response to this need, CWS have emerged as a solution providing flexibility, collaboration, and productivity support. CWS offer shared work environments for various professionals, including creative economy players, SMEs, freelancers, employees, executives, and students. This research employs qualitative and quantitative methods through a literature review involving sources from different countries. The growth of CWS in various cities worldwide brings legal implications requiring special regulations due to their distinct characteristics and usage purposes compared to traditional offices. Additionally, perspectives from human resource management, marketing, entrepreneurship, and legislation provide various recommendations for the future development of CWS, encompassing community, motivation, and collaboration. Overall, coworking spaces offer an innovative solution for modern work needs, support the development of the creative economy, and require specific attention in regulation and management to ensure their sustainability and growth